Analysis of research articles using passive voice in the conclusion sections - Djuwari, Djuwari; Prestoza, Mark Jhon (AJELP: Asian Journal of English Language and Pedagogy, 2024)
Many researchers always get notified while composing sentences on a computer and checking grammar using the review and spelling check menu. They experience this notification frequently when typing passive sentences. They are always suggested to revise passive sentences into active sentences. In the conclusion sections of research journal articles, authors sometimes contemplate the necessity of sticking to active sentences. This research aims to investigate the prevalence of passive construction in articles authored by research articles (RAS) published in the international journals. Specifically, purposive sampling was employed by the researchers to select the conclusion sections as the sample sub-genres. It is presumed that all articles underwent blind review, ensuring homogeneity in their academic status. The 10 articles with their conclusion sections (3,962 words) were analyzed after being selected based on certain criteria such as being published and found in Google Scholar website. The findings reveal that authors in research articles still use passive sentences. This pattern is observed in each of the RAS for the purposes of presenting information, describing actions and results, maintaining objectivity, and emphasizing the content (objects being discussed) rather than the doers.